Love in social care: necessary pre-requisite or blurring of boundaries - John Byrne (Scottish Journal of Residential Child Care)
This article is a practice reflection on the theme of love in social care. It explores the personal qualities required for social care practice and the role of a social care worker in residential child care . A definition of love is provided, and comparisons are made between the concepts of love and compassion. Questions are raised about the the issue of boundaries in the professional helping relationship and the impact of defensive practice on children's emotional development. The article concludes that love and compassion are essentially the same thing, and that since compassion is a necessary pre-requisite for the work, love is, and always will be a the core of everything we do.